THE EFFECT OF APPLYING CONTEXTUAL LEARNING MODELS IN LEARNING WRITING NARRATIVES AT SMP KARTIKA XXI MAKASSAR - Mutmainnah, Mutmainnah (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
This research uses quantitative research methods with experiments. Using a one group pre-test post-test design. The data analysis used was the T-test with results showing that it was 0.841 and the t-table was 0.684. Because t-count ≥ t-Table = 0.841 ≥ 0.684 and it can be concluded that it is rejected and based on the criteria of significant examiner rules which say if t-Count ≥ t.Table then it is rejected and accepted which means it can be influenced by the application of the Contextual learning model in learning to write narratives and if t-Count < t-Table then it is accepted and rejected, meaning there is no influence on the application of the contextual learning model in learning to write narratives at SMP Kartika XXI Makassar .